Bureaucratic Frictions and Innovation Procurement - Leonardo M. Giuffrida; Emilio Raiteri (Center for Economic Studies and ifo Institute (CESifo), 2023)
Is work overload a friction to public agencies? Using data on R&D procurements, patents, and contracting units from a US federal agency, we investigate how officer workload impacts innovation procurement outcomes. Unanticipated retirement shifts provide an exogenous source of variation that we exploit as an instrument for workload. When workload declines, we find a significant increase in patent rates. One additional officer leads to a 28 percent increase in the probability that a contract will generate a patent. Our findings suggest that officers burdened with excessive workloads may not provide adequate guidance to R&D suppliers when it is most needed.
Keywords: D23; D73; H57; J24; O31; 330; workload; procurement; bureaucrats; R&D; patents; instrumental variable